(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
An analysis of the covariance and spectral structure of the Hilbert transform of biperiodically non-stationary random processes, which are a model of signals with double rhythmicity, are provided. The obtained relations for the cross-covariance and cross-spectral characteristics of the signal and its Hilbert transform. Наведено аналіз кореляційної та спектральної структури перетворення Гільберта біперіодично нестаціонарних випадкових процесів, які є моделлю сигналів із подвійною ритмічністю. Отримано співвідношення для взаємокореляційних та взаємоспектральних характеристик сигналу та його перетворення Гільберта.